MEMAKNAI IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY MENUJU SUSTAINABILITY DALAM PERSPEKTIF SOCIAL PRACTICE BOURDIEU - Rochayatun, Sulis (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This study aims to interpret the implementation of CSR in achieving corporate sustainability studied with Bourdieu's social practice theory. This study uses an interpretive paradigm with a phenomenological approach. The research location is PT. Tirta Investama - Pasuruan Keboncandi Factory. Data collection was carried out by conducting in-depth interviews with key Â informants who took turns to obtain data triangulation.The results showed that the implementation of CSR on the research site was well organized and structured and became a permanent and incidental program. CSR is implemented based on the principle of